THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL BEHAVIOR ON INVESTMENT DECISION - NUGRAHA, RIFQI KURNIA; EKSANTI, ARLINA PUTRI; HALOHO, YUSTUS ODEMA (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2022)
This research is a quantitative research which aims to determine the effect of financial literacy and financial behavior on investment decisions. The population in this study were active students at Mercu Buana University, Jakarta. The sample is 43 respondents. Non-probability sampling method, purposive sampling. Data collection is done by distributing questionnaires to a predetermined sample via google form. The data analysis technique used the PLS (Partial Least Square) analysis method with SmartPLS 3.0 software. The results of this study indicate that: (1) Financial literacy has an influence on investment decisions with a path coefficient value of 0.338 (2) Financial behavior has an influence on investment decisions with a path coefficient value of 0.509.